‘A proud daughter of this fusion’: October 12th and the battle for the meaning of an uncomfortable anniversary (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2025)
What do we remember when we commemorate October 12th? How is this date inscribed, commemorated and taught in schools? What are the tensions between school teaching and the contested construction of a collective memory? This event was renamed "Day of Respect for Cultural Diversity" in Argentina in 2010. The phrase cited in the title was published on Twitter/X in October 2023 by Vice President Victoria Villarruel (then a candidate), celebrating "Hispanic Heritage Day" and establishing a relationship between the commemorated event and the construction of her own identity. In this paper, we explore the link between the official objectives of the anniversary over time, school practices and celebrations based on surveys of practicing teachers, retirees, and teacher training students. Finally, we analise public disputes surrounding the meaning of the event in the speeches of prominent political figures of the last five years.
Keywords: anniversary; October 12th; school celebrations; collective memory; diversity